A new technique of intraoperative prevention of infectious complications during penile prosthesis implantation - S. V. Popov; E. Lledo-Garcia; I. N. Orlov; T. M. Topuzov; P. S. Kyzlasov; D. V. Gribanov; I. Yu. Pestryakov (Вестник урологии)
Penile prosthetics is the «gold standard» for treatment of severe or drug-induced refractory erectile dysfunction. One of the most formidable postoperative complications of penile prosthetics is periprosthetic infection. Currently, infusion and topical application of broad-spectrum antibacterial drugs is used for the prevention of prosthetic infectious complications. One of the means for the prevention of postoperative infectious complications is the Alexis retractor (Applied Medical, Rancho Santa Margarita, CA). It is a port that is installed in the surgical area and limits the contact of the prosthesis components with the surrounding tissues and skin, achieving optimal wound visualization. The use of Alexis provides atraumatic retraction of the wound edges and 360-degree protection of the wound from the contact of the implant components with adjacent tissues and skin.